Knjižni jezik zožiti na jezikovni standard?! - Žele, Andreja (Slavia Centralis, 2020)
Reducing Standard Literary Language to a Linguistic Standard?!The paper is determining why the so-called standard language cannot and must not replace standard literary Slovenian. It discusses the lack of comprehensive knowledge about the phenomenon that is standard literary language, touching especially on the poor understanding of its complex developmental processes and its social function in the broadest sense (social-historical, moral and ethical). The distinction between standard literary and standard language remains blurred in the Slovenian environment; missing are short linguistic definitions that would establish transparent criteria for subsequent descriptions and the specific use of both concepts.
Keywords: standard literary Slovenian; language standardization; linguistic norm; cultivated and cultural speech